Epidemiological features of traumatic spinal cord injury in Wuhan, China - Fater A. Khadour; Younes A. Khadour; Ling Meng; Cui Lixin; Tao Xu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Spinal cord injuries are extremely debilitating and fatal injuries. There is currently little research focusing on traumatic spinal cord injuries, and there is little information available about the epidemiological characteristics of patients with traumatic spinal cord injury (TSCI). Objective To describe the epidemiological features of traumatic spinal cord injury in Wuhan, China. Design A retrospective hospital-based study. Setting Rehabilitation department of Wuhan's Tongji Hospital. Participants People who had been diagnosed with a traumatic spinal cord injury (TSCI) were admitted to Tongji Hospital from 2016 to 2021 (n = 463). Interventions Not applicable. Outcome measures: Epidemiological features such as sex, age, marital status, etiology, occupation, neurological level of injury, and the American Spinal Injury Association Impairment Scale on admission, hospitalization, and concomitant injuries were collected. Results The mean age of patients with TSCI was 39.4 ± 14.3 years, and the male/female ratio was 3:1. The leading causes of TSCIs were traffic accidents (38.4%), followed by falls (low falls 24.0%, high falls 13.2%). The most common injury site was the cervical spinal cord, followed by the thoracolumbar level. Of all patients, 463 patients (67.2%) had complications and other injuries. During the hospitalization period, a total of 217 patients experienced complications, with a percentage of 46.9%. Urinary tract infection was the most common (15.6%), followed by pulmonary infection (14.0%). Conclusion The results found that the proportion of males was greater, and the first two main reasons were falls and traffic accidents. Farmers and workers are the occupations most vulnerable to SCI. We need to pay more attention to the elderly's risk of falling. These findings suggested that preventive strategies should be based on the features of different types of TSCI patients. Finally, the importance of SCI rehabilitation must be highlighted.